Correlation Between Glycosylated Haemoglobin and Thyroid Function Tests in Patients with Type-2 Diabetes Mellitus - Qaisar, Ayesha; Sultana, Riffat; Ayub Khan, Jibran Umar (Journal of Gandhara Medical and Dental Science, 2019)
ABSTRACT: OBJECTIVES: The aims of this study were to determine the frequency of undetected dysfunction of thyroid in patients with diabetes, determination of correlation between glycosylated Hb and thyroid hormones, and to find out the relationship between blood glucose control and function of thyroid in patients of type 2 diabetes mellitus in comparison to normal individuals. METHODOLOGY: This study was carried out at Department of Medicine, Hayatabad Medical Complex, Peshawar. It was a cross sectional study. A sample size of 358 subjects was taken using non-probability consecutive sampling in which 179 had type-2 diabetes and 179 were healthy normal subjects. Based on the results, they were classified into either hypothyroid or hyper thyroid categories, and then a comparison was done with HbA1c to determine their correlation. The data was analyzed by using SPSS version 23. RESULTS: The mean age of both the groups was 54.35 ± 9.38 years and 42.66 ± 9.20 years respectively on comparison of median (as data lacked normality) and mean ages of cases was much higher as while drawing comparison to control group with p-value less than 0.001. In these cases, the total number of male patients were 62 (34.64%) and females were 117 (65.36%) while in controls the males and females were 124 (69.27%) and 55 (30.73%) respectively. In these cases, the number of hypothyroid patients were 13 (7.3%), hyperthyroid individuals were 26 (14.5%) and 11(6.1%) cases had subclinical hyperthyroidism. Normal thyroid function was found in all controls. In these cases, a weak positive correlation was found between HBA1c and T3 (r=0.239, p-value 0.001). Also, there was an insignificant correlation with T4 (r= - 0.017, p-value = 0.817) and correlation of insignificant nature found with TSH (r= -0.036, p-value = 0.634). Among controls same (insignificant) correlation was found between Glycosylated Hb and T3 (r= 0.070 p-value = 0.352), a weak positive correlation with T4 (r= 0.238, p-value = 0.001) and a moderate negative relationship with thyroid stimulating hormone (r= - 0.586, p-value <0.001). CONCLUSION: Early detection of thyroid dysfunction in diabetic patients can prevent complications and leads to optimum control of blood glucose level.